Changes in Photosynthetic Electron Transport during Leaf Senescence in Two Barley Varieties Grown in Contrasting Growth Regimes. (4th September 2020) - Shimakawa, Ginga; Roach, Thomas; Krieger-Liszkay, Anja
Abstract: Leaf senescence is an important process for plants to remobilize a variety of metabolites and nutrients to sink tissues, such as developing leaves, fruits and seeds. It has been suggested that reactive oxygen species (ROS) play an important role in the initiation of leaf senescence. Flag leaves of two different barley varieties, cv. Lomerit and cv. Carina, showed differences in the loss of photosystems and in the production of ROS at a late stage of senescence after significant loss of chlorophyll (Krieger-Liszkay etal. 2015 ). Here, we investigated photosynthetic electron transport and ROS production in primary leaves of these two varieties at earlier stages of senescence. Comparisons were made between plants grown outside in natural light and temperatures and plants grown in temperature-controlled growth chambers under low light intensity. Alterations in the content of photoactive P700, ferredoxin and plastocyanin (PC) photosynthetic electron transport were analyzed using in vivo near-infrared absorbance changes and chlorophyll fluorescence, while ROS were measured with spin-trapping electron paramagnetic resonance spectroscopy. Differences in ROS production between the two varieties were only observed in outdoor plants, whereas a loss of PC was common in both barley varieties regardless of growth conditions. We conclude that the loss of PC is the earliest detectable photosynthetic parameter of leaf senescence while differences in the production of individual ROS species occur later and depend on environmental factors.